PENERAPAN MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS V SDN 004 LOBOK OGONG KECAMATAN BANDAR SEI-KIJANG - Susi Eva Wanti; Otang Kurniaman; Lazim N ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study was conducted because of the low reading comprehension on the subjects of Indonesian students in grade V SDN 004 Lobok Ogong Kecamatan Bandar Sei-Kijang. KKM set in schools, namely 75. Of the 20 students, who reached the KKM is just 8 students (40%), while students who have not reached the KKM is 12 students (60%) with an average grade of 60. The purpose of the study is to improve students' reading comprehension class V SDN 004 Lobok Ogong Kecamatan Bandar Sei-Kijang by implementing cooperative learning model of integrated reading and composition. The results obtained by the average value of the basic score of 60 in the first cycle increased by 15% to 69. In the second cycle the average value of students also increased by 35% to 81. Development of the group at the first meeting of the first cycle there are 4 groups of either category, and second there is one group of either three great groups, the first meeting of the second cycle was obtained 2 super group and the second group obtained a second meeting next great 4 super group. Analysis of the ability of individual students' reading comprehension at the first meeting I cycle there is a category of high 0, the medium category there are 7 students and 13 students lower category. Later in the second meeting of the first cycle are included in the high category 2 students, the moderate category 5 students and the low category, there were 13 students. The first meeting of the second cycle is increased in the high category there are 7 students, a category was 6 students while the lower category 7 students. The second meeting of the second cycle of high class 12 students and 8 students category were lower category 0. Activities of teachers at the first meeting of the first cycle percentage is 53.57% with the category Fairly. The second meeting increased to 71.42% in both categories. At the first meeting of the second cycle of teacher activity increased to 78.57% with the category very well. At the second meeting increased to 82.14% with the category very well. Activities of students at the first meeting of the first cycle percentage is 42.85% with less category. The second meeting increased to 50% by category, please. At the first meeting of the second cycle of student activity increased to 64.28% in both categories. At the second meeting increased to 71.42% with the category very well.Keywords : cooperative integrated reading and composition, reading comprehension